Proceedings of the 2017 CHI Conference on Human Factors in Computing Systems 2017
DOI: 10.1145/3025453.3025817
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Sources and Types of Smartwatch Usage Sessions

Abstract: We seek to quantify smartwatch use, and establish differences and similarities to smartphone use. Our analysis considers use traces from 307 users that include over 2.8 million notifications and 800,000 screen usage events, and we compare our findings to previous work that quantifies smartphone use. The results show that smartwatches are used more briefly and more frequently throughout the day, with half the sessions lasting less than 5 seconds. Interaction with notifications is similar across both types of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 38 publications
4
28
0
Order By: Relevance
“…Results of studies used in the smartwatch UX profile are in line with each other's and other recently reported smartwatch usage studies. Smartwatches' ease of access is highlighted by the fact that smartwatch users had on average 142.1 usage sessions per day compared to smart phones' 60.1 times per day according to study by Visuri et al [4]. In all studies most common smartwatch activity has been watch usage i.e.…”
Section: Smartwatch Ux Profilementioning
confidence: 99%
“…Results of studies used in the smartwatch UX profile are in line with each other's and other recently reported smartwatch usage studies. Smartwatches' ease of access is highlighted by the fact that smartwatch users had on average 142.1 usage sessions per day compared to smart phones' 60.1 times per day according to study by Visuri et al [4]. In all studies most common smartwatch activity has been watch usage i.e.…”
Section: Smartwatch Ux Profilementioning
confidence: 99%
“…Our findings are supported by a quantitative study of smartwatch use, which found that wearers had fewer unprompted interactions than with smartphones. 7 Some study participants also valued the opportunity to read messages on their smartwatches, without sending the other person awareness cues 11 such as read receipts or notices showing when they were last online. Apps like WhatsApp or Facebook Messenger automatically enable these cues to create the illusion of having real-time conversations, but from the user's perspective, noted one participant, they can serve as "added pressure."…”
Section: Smartwatches As Magic Braceletsmentioning
confidence: 99%
“…6 Indeed, recent research suggests that users are just as likely to interact frequently with their smartwatches as they are with their smartphones. 7 Is there any evidence that smartwatches have these negative impacts on users? Do they really exacerbate expectations of being online?…”
mentioning
confidence: 99%
“…Most smartwatch users were found to briefly read messages on their smartwatch and then read them again on their smartphone because of the inconvenient and limited input capabilities of smartwatches. Additionally, Visuri et al () argued that smartwatches are more suitable for content consumption than content creation owing to the limited input capabilities of smartwatches. In summary, the main function of smartwatches is notification and due to input limitations, smartwatches are used as an auxiliary device.…”
Section: Introductionmentioning
confidence: 99%